#### Answer

53

#### Work Step by Step

We are given that $f(x)=x^{2}+4$, $g(x)=2x+3$, and $h(x)=x-5$.
We are asked to find $(f∘h)(-2)$. We know that $(f∘h)(x)=f(h(x))$.
Therefore, $(f∘h)(-2)=f(h(-2))=f(-2-5)=f(-7)=(-7)^{2}+4=49+4=53$.

Published by
Pearson

ISBN 10:
0321969359

ISBN 13:
978-0-32196-935-4

53

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.